Discursos sobre o ensino e aprendizagem de língua inglesa na escola pública: entre arborescências e transformações - Ladeira, Eliana de Sousa Andrade (2022)
This dissertation as a result of our affection aimed to expose the cartographic-discursive research proposal that is carried out in it. We present the analysis of some statements on the teaching-learning processes of English as a foreign language of students and teachers from a K-12 public school. Our aim was to understand the meanings that they attribute to it and in/by which discourses, and to verify, more particularly, if, as we hypothesized in the project, fear would be one of the meanings expressed in relation to speaking the language. To conduct our study, one questionnaire was applied for teachers and another for students. Their answers were then transcribed, forming our corpus. The proposal called AREDA (Analysis of Discursive Resonances in Open Statements), developed by Serrani (2001) and which aims to “study non-cognitive factors and identification processes of insertion in foreign languages” (SERRANI, 2001, p. 247) was our guiding methodology. For the composition of this work, we also mobilized theoretical assumptions of Discourse Analysis, Applied Linguistics and Spinoza's Philosophy in order to build a critical look at issues related to the teaching and learning of the English language and power relations and knowledge related to that language and in the contemporary context of the public-school classroom. From this perspective, we understand that some meanings have been constructed throughout the history of teaching and learning the language with dichotomous and colonial sayings that subordinate us as subjects of knowledge. In addition, we are inspired by the Deleuzo-Guattarian’s rhizomatic thought proposal, by which we are affected in a second moment of our study path, and from which we set out to perform cartographic movements in the research corpus. By cartographic movements, we understand the way of reflection of the researcher who, despite following methodological guidelines in dealing with language in the corpus and with meanings that refer to arborescent functions, in Deleuzo-Guattarian terms, is free to extrapolate these delimitations and expand her interpretations, being available to see the movements of transformation in the arborescent processes.